The incidence of Down's syndrome over a 19-year period with special reference to maternal age. - Owens, J R (1983)
The incidence of Down's syndrome in the Liverpool and Bootle areas from 1961 to 1979 was investigated. A total of 319 liveborn cases was ascertained over this period. Using 3-year moving averages, the incidence of the condition fell gradually from 1.62 per 1000 livebirths for 1961 to 1963 to 1.09 per 1000 livebirths for 1977 to 1979. This trend is significant at the 0.1% level. Over the same period the mean maternal age of Down's syndrome births fell gradually from 36.7 years in 1961 to 29.0 years in 1979. This trend is significant at the 1% level. There was a contemporaneous decrease in the proportion of total births to women over 35 years in the study area. Cytogenetic analysis was performed on 175 out of the 319 index cases (54.9%). Of these, there were 161 trisomies (92%), 11 translocations (6.3%), and three mosaics (1.7%). Between 1969 and 1979 four terminations of pregnancy for Down's syndrome were performed, all for trisomy. Quinquennial age specific incidences for Down's syndrome were calculated for the years 1960 to 1964, 1965 to 1969, 1970 to 1974, and 1975 to 1979. There have been no statistically significant changes over this time. It is suggested that the fall in incidence of Down's syndrome can be explained by the fall in mean maternal age.